2002
DOI: 10.1046/j.0953-816x.2001.01844.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent inhibition of hippocampal LTP in vitro following contextual fear conditioning in the rat

Abstract: The effects of contextual fear-learning on hippocampal synaptic excitability were investigated by means of high frequency tetanic stimulation (HFS) in rat brain slices (hippocampal CA1 region), prepared at different intervals (immediately, 24 h or 7 days) after a one-trial contextual fear conditioning paradigm session. In the latter, rats that had previously received aversive electrical footshocks in the experimental apparatus exhibited freezing (the conditioned response) when placed again in the same apparatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
61
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 47 publications
12
61
1
Order By: Relevance
“…This approach has been taken to establish, for example, that one-trial learning in the hippocampus [48,49] induces plasticity akin to LTP. A biochemical signature of LTD is the loss of surface expressed AMPAR and concomitant changes in AMPAR subunit phosphorylation at specific residues, and these same changes have been observed in visual cortex following brief MD [50].…”
Section: Ocular Dominance Plasticitymentioning
confidence: 99%
“…This approach has been taken to establish, for example, that one-trial learning in the hippocampus [48,49] induces plasticity akin to LTP. A biochemical signature of LTD is the loss of surface expressed AMPAR and concomitant changes in AMPAR subunit phosphorylation at specific residues, and these same changes have been observed in visual cortex following brief MD [50].…”
Section: Ocular Dominance Plasticitymentioning
confidence: 99%
“…Synaptic changes were localized to vermal lobules V and VI, an area that receives convergence of acoustic and nociceptive stimuli Stowell 1944 andSaab andWillis 2003) and it is related to the expression of emotional behavior Sebastiani et al 1992). Learning-induced synaptic plasticity has been described in amygdala (Rogan et al 1997 andMcKernan andShinnick-Gallagher 1997) and hippocampus (Sacchetti et al 2001, Sacchetti et al 2002band Whitlock et al 2006. Thus, fear learning may be associated with similar neural mechanisms in several different brain structures.…”
Section: Neural Basis Of the Cerebellar Involvement In Learned Fearmentioning
confidence: 97%
“…Given that LTP is considered a physiological cellular model of learning and memory formation (Martin et al, 2000;Sacchetti et al, 2002;Gruart et al, 2006;Morris, 2006) and that one-trial inhibitory avoidance training was shown to induce LTP in CA1 in vivo (Whitlock et al, 2006), we used this task to test the prediction that a behavioral analog of the synaptic tagging and capture hypothesis, a key property of synaptic plasticity, occurs in vivo.…”
Section: Discussionmentioning
confidence: 99%